PENGARUH INOKULASI BAKTERI PENGHASIL ACC DEAMINASE TERHADAP INFEKSI AKAR DAN PRODUKSI SPORA PADA PERBANYAKAN MIKORIZA - , NURUL IZZATI SHIFA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The aim of this work was to determine the effect of inoculation of ACC deaminase -producing bacterium on the degree of root infection and spore production in arbuscular mycorrhizal propagation using maize as a host plant. In this study were used 6 corn varieties consisting of local varieties (Talangoh , guluk - guluk and Manding) yielding variety (Bisma) and hybrid varieties ( Bisi Bisi 2 and 816 ) . Greenhouse studies was conducted using Split Plot Design (3x6) with 3 replications. The first factor was the inoculation treatment as the main plot factor consisting of 3 treatments : (1) without inoculation , (2) mycorrhizal inoculation and (3) mycorrhizal inoculation + ACC deaminase-producing bacterium. The second factor was the variety as the subplot factor, consists of six varieties. Data were analyzed by DMRT (Î± = 5 %). The results showed that the inoculation of ACC deaminase-producing bacteriumincreased root infection and spore production in all varieties of maize used in this study, and the highest yield obtained in Bima variety. Inoculation of ACC deaminase-producing bacterium also increased maize growth in all varieties. Our results indicate that inoculation of ACC deaminase-producing bacterium can be used to improve quality in arbuscular mycorrhizal propagation using culture pot technique.